Human factors visualization and storytelling design questionnaire: validity and reliability tests - Mohd Zanan, Muhammad Faris Basheer; Sheikh Abdul Aziz, Madihah (RMP Publications, 2022)
In the era of data and the quest for data-driven decision-making, the capacity to tell stories from data is proving to be increasingly valuable. Storytelling is not only a great method displaying facts, but also an effective approach to package knowledge and information so that everyone can understand it. While numerous tools are available to produce a strong storytelling visualization at the moment, the tools' ability to be personalized by the user is almost non-exist. To determine the connection between personality and user preferences toward different visual designs, this study employs the user preferences on visual design related to the data visualization questionnaire that was used in the previous research. In this research, the data storytelling element was added; hence the questionnaire needs to be evaluated based on validity and reliability test. In this paper, the validity and reliability tests of the questionnaire will be explained thoroughly. The outcome of this test will help in producing a questionnaire that is valid and reliable for upcoming research related to the field.